Career Adaptability and Subjective Well-Being in Unemployed Emerging Adults: A Promising and Cautionary Tale. (December 2015) - Konstam, Varda; Celen-Demirtas, Selda; Tomek, Sara; Sweeney, Kay
Unemployment is associated with increased levels of anxiety, depression, and disconnection among emerging adults. Given the greater risk of unemployment for emerging adults (13.2% in the United States), career adaptability is relevant to understanding how emerging adults survive and thrive in today's challenging work environment. This study examined the effect of career adaptability on subjective well-being in 184 unemployed diverse emerging adults of age 21–29. Results revealed that emerging adults with higher levels of control and confidence had higher life satisfaction. Control was positively related to positive affect while at the same time negatively related to negative affect. Control was the most consistent informant of subjective well-being (significant on all three subscale measures). The implications of the significant findings, and the caution warranted in relation to these findings, are discussed.